2019
DOI: 10.1002/cphc.201801098
|View full text |Cite
|
Sign up to set email alerts
|

pH Dependence ofT1for13C‐Labelled Small Molecules Commonly Used for Hyperpolarized Magnetic Resonance Imaging

Abstract: Hyperpolarization is a method to enhance the nuclear magnetic resonance signal by up to five orders of magnitude. However, the hyperpolarized (HP) state is transient and decays with the spin‐lattice relaxation time (T1), which is on the order of a few tens of seconds. Here, we analyzed the pH‐dependence of T1 for commonly used HP 13C‐labelled small molecules such as acetate, alanine, fumarate, lactate, pyruvate, urea and zymonic acid. For instance, the T1 of HP pyruvate is about 2.5 fold smaller at acidic pH (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…1 (C)). The polarization was much weaker at pH 2.5, suggesting a possible role for hydrogen bonds among NAC clusters in reducing the equilibrium polarization 25 , 30 . The T 1 relaxation time at 3 T of the 3.2 M [1- 13 C] NAC solution was determined to be 19.6 s by the decay dynamics of 13 C MR signal (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1 (C)). The polarization was much weaker at pH 2.5, suggesting a possible role for hydrogen bonds among NAC clusters in reducing the equilibrium polarization 25 , 30 . The T 1 relaxation time at 3 T of the 3.2 M [1- 13 C] NAC solution was determined to be 19.6 s by the decay dynamics of 13 C MR signal (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Samples using a standard solvent of DMSO 25 polarized poorly (Fig. 1 B), possibly because the anhydrous solvent favors the formation of intermolecular hydrogen bonds between two protonated carboxylic acid, which would increase the dipolar coupling associated with the carbonyl carbon and shorten T 1 relaxation 30 . To reduce intermolecular association, [1- 13 C] NAC was titrated to a neutral pH of 7.5 using 5 M NaOH.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with other ( 15 N) 3 -azide-tagged compounds (i.e., 1-3 and 6), signal enhancements of 4 and 5 were largely affected by the acidity of the compounds. 23 Hyperpolarization of ( 15 N)3azidotyrosine 4 ( = ~142,000) and ( 15N) 3 -azidoalanine 5 ( = 80,000) was improved significantly by adding concentrated NaOH to neutralize a solution of their conjugate acids. The favorable polarization lifetime observed on ( 15 N)3-azidotyrosine 4 and ( 15 N)3-azidoalanine 5 suggested that the ( 15 N)3-azidotagging strategy offers an innovative platform, alternative to previous 15 N-labeled examples, 24 to design a diverse range of hyperpolarized amino acid imaging probes.…”
Section: Hyperpolarization Of ( 15 N)3-azide-tagged Molecules Using D-dnpmentioning
confidence: 99%
“…We used the acquisition scheme in Figure 1E to probe the 13 Chyperpolarizationc reatedi nt he ethyl esters 4a,b and in the free amino acids 5a,b on the same samples, with representative spectra shown in Figure 2. [12] Since the ester hydrolysis step was performed by manuali njection of the NaOD solution and because its overall length was determined by sample homogenization,w ee xpect that losses can be reduced under optimal hydrolysis conditions. We refrain from estimating the expected loss during this step, notingt he strong pH dependence of the 13 C-T 1 in a-aminoa cid.…”
mentioning
confidence: 99%
“…We refrain from estimating the expected loss during this step, notingt he strong pH dependence of the 13 C-T 1 in a-aminoa cid. [12] Since the ester hydrolysis step was performed by manuali njection of the NaOD solution and because its overall length was determined by sample homogenization,w ee xpect that losses can be reduced under optimal hydrolysis conditions.…”
mentioning
confidence: 99%